Social Media Use Time and Mental Health of Young Adults: A Cross‐Sectional Study in Bangladesh - Sudipta Das; Abdullah Al Zubayer; Marzia Feruz Snigdha; Md. Fahim Uddin; Mubin Khan Afridi; Kazi F. J. Kanak; Mohammad Kibria; Afroja Akter; Israt Jahan; Ashfia M. Rafa; Hasan M. Kamran; Safayet Jamil; et al. (Health Science Reports, 2025)
ABSTRACT Background Social media (SM) use has gained much popularity among young adults, which could impact their mental health. The association between SM use time and young adults' mental health in Bangladesh has been less researched. Aim To determine the association between SM use time and mental health among young adults in Bangladesh. Methods Cross‐sectional data were collected from 440 young adults aged 18–35 from two districts in Bangladesh: Dhaka and Cumilla. Data were collected using a self‐reported questionnaire, including their socio‐demographic characteristics, SM use time, and mental health disorders—depression and anxiety. Depression and anxiety were assessed by PHQ‐9 and GAD‐7, respectively. SPSS version 22 was used to perform data analysis. Results Of the 440 participants, 29.5% used SM for < 2 h/day, 36.6% used for 2–4 h/day, and 33.9% used for > 4 h/day. The crude analysis showed that participants who used SM for > 4 h/day had significantly higher odds of depression than those who used < 2 h/day (OR = 2.094, 95% CI: 1.245, 3.522, p = 0.005). The association also remains significant after adjusting for socio‐demographic variables (OR = 2.158, 95% CI: 1.241, 3.753, p = 0.006). Also, this study showed that using SM for > 4 h/day was associated with increased odds of anxiety both in crude and adjusted models (OR = 1.864, 95% CI: 1.041, 3.337, p = 0.036) and (OR = 1.945, 95% CI: 1.054, 3.587, p = 0.033), respectively. Conclusion This study shows that using SM for more than 4 h a day is significantly associated with higher odds of depression and anxiety among young adults. A more robust study should be carried out to determine the setting limits for daily SM use that could help reduce the burden of mental health disorders among Bangladeshi young adults.